A Python program for the implementation of the Γ-method for Monte Carlo simulations - De Palma, Barbara; Erba, Marco; Mantovani, Luca; Mosco, Nicola (Computer physics communications, 2019)
We present a modular analysis program written in Python devoted to the estimation of autocorrelation times for Monte Carlo simulations by means of the Γ-method algorithm. We give a brief review of this method and describe the main features of the program. The latter is characterized by a user-friendly interface and an open source environment which, along with its modularity, make it a versatile tool. Finally we present a simple application as an operational test for the program. Program Title: UNEW Program Files doi:http://dx.doi.org/10.17632/hvtvnjsg3h.1 Licensing provisions: MIT Programming language: Python Nature of problem: Computation of autocorrelation time for Monte Carlo generated data in an open source environment. Solution method: Modular package implementing the Γ-method with advanced data handling.